Propostas para a atualizaç\~ao da legislaç\~ao migratória brasileira: Princípos norteadores, direitos e garantias, deveres, impredimentos e restriç\~oes - Guilherme de Oliveira Schmitz (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– In the Congress, there are two Bills going through for amend the 1980's Immigration law. For that, the political debate on immigration law has gained strength among the various groups of interest in the subject, as it matures the perception that current legislation does not correspond to the values and interests of Brazilian society. In this context, this work aims to comparatively analyze the two Bills to amend the Foreigners' Statutes, which both intent to make Brazil more attractive to immigrants and improve the entry procedures of these. That way, it is intended to contribute, in its legal dimension, to the adequacy of migration policy to the social reality of Brazil.
Keywords: K37; 330; migration; international human mobility; immigration law